Produção de massas alimentícias no município de Jucurutu-RN: um estudo de caso - Martins, Higor Breno de Oliveira (Universidade Federal Rural do Semi-Árido, 2020)
The pasta production sector in Brazil is currently under development, being of great importance for the economy and food of the country, Rio Grande do Norte, especially, the municipality of Jucurutu deserves prominence in this branch of activity, as it has stood out a important regional pole in this type of production. Given the importance of this activity, this work aims to demonstrate the simple way in which pasta production at Industria Massas Jucurutu works and understand its contribution to the municipality of Jucurutu. A questionnaire was prepared to interview the company's managers and employees, to describe the company's mass production processes, and a photographic and descriptive survey of the equipment was carried out. based on quality studies and on the benefits that this activity promotes for the municipality, among the data provided, it considers that its main distinguishing feature in the market is the quality of the product itself and the marketing that is widely applied. As the industry thrives, the municipality gains in several factors, both economic and tourism, considering Indústria Massas Jucurutu a beneficial economic agent for the municipality of Jucurutu-RN.
Monografia
Keywords: Indústria; Massas; Produção; Alimentação; Economia; Industry; Pasta; Production; Food; Economics; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA